2020
DOI: 10.1074/jbc.ra120.012730
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of fatty acid transport protein 2 (FATP2) in the mouse liver changes the metabolic landscape by increasing the expression of PPARα-regulated genes

Abstract: Fatty acid transport protein 2 (FATP2) is highly expressed in the liver, small intestine, and kidney, where it functions in both the transport of exogenous long-chain fatty acids and the activation of very-long-chain fatty acids. Here, using a murine model, we investigated the phenotypic impacts of deleting FATP2, followed by a transcriptomic analysis using unbiased RNA-Seq to identify concomitant changes in the liver transcriptome. WT and FATP2-null (Fatp2−/−) mice (5 weeks) were maintained on a standard chow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…In contrast to this report, we observed no significant effect of FATP2 deletion on hepatosteatosis, perhaps reflecting the relatively modest liver disease in Slc27a2 +/+ Lepr db/db eNOS -/mice, differences in genetic background, and/or differences between acute shRNA knockdown versus chronic gene deletion. On the other hand, Slc27a2 -/mice on normal chow demonstrated increased liver fatty acid content and lipid droplets (46), which is consistent with our data (Supplemental Figure 11B). Of other possible extrarenal FATP2 effects, a recent report demonstrates that FATP2-dependent arachidonic acid uptake activates a subset of neutrophils involved in cancer pathophysiology (47).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to this report, we observed no significant effect of FATP2 deletion on hepatosteatosis, perhaps reflecting the relatively modest liver disease in Slc27a2 +/+ Lepr db/db eNOS -/mice, differences in genetic background, and/or differences between acute shRNA knockdown versus chronic gene deletion. On the other hand, Slc27a2 -/mice on normal chow demonstrated increased liver fatty acid content and lipid droplets (46), which is consistent with our data (Supplemental Figure 11B). Of other possible extrarenal FATP2 effects, a recent report demonstrates that FATP2-dependent arachidonic acid uptake activates a subset of neutrophils involved in cancer pathophysiology (47).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, study has shown that SLC27A2 ablation can restore FAO-related key enzymes activity caused by kidney damage, and protect TECs from lipotoxicity 28 . Deleting FATP2 in the mouse liver also found it changes the metabolic landscape by increasing the expression of PPARα 27 . Interestingly, PPAR signaling pathway can be downregulated by TGF-β in almost all fibrotic tissues [46][47][48] .…”
Section: Discussionmentioning
confidence: 96%
“…However, when mice were fed a lipogenic methionine choline-deficient diet for 4 weeks, FATP2 and 5 were marginally decreased, although increases in FATP 1 and FATP4 were noted [29]. Apart from any dietary stimulus, the genetic deletion of FATP2 in the liver provokes commensurate increases in CD36 and FATP1 expression, indicating compensatory mechanisms to coordinate and regulate the uptake of lipids [27]. Although we did not investigate the complete profile of fatty acid uptake systems in our CD-HFD model, we deduce that the negative correlation between exercise and hepatic lipid accumulation was independent of the changes in FATP2, FATP5, and CD36.…”
Section: Discussionmentioning
confidence: 97%
“…The upregulation of CD36 is consistent with the increase in plasma and hepatic FFA levels ( Figure 4 and Figure 5 ) and is a feature observed in other experimental models [ 25 , 26 ]. This increased CD36 expression promotes the accumulation of unsaturated FAs, which are a driving force for steatotic triglyceride formation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation